Sexual Homicide in France and Canada: An International Comparison - Chopin, Julien (Journal of interpersonal violence, 2021)
Despite a recent increase in the number of studies published on sexual homicide (SH), several of these studies have been based on small and nonrepresentative samples. This study aims to describe and compare two samples of SH from France (n = 412) and Canada (n = 350) where data have been collected and coded with the same tool. The data include variables related to the crime, the offender, and the victim characteristics. The overarching goal is to further the knowledge about French SH and to assess the possibility of merging French and Canadian cases to create a cross-national database of 772 cases of SH. Among the 126 variables included in the comparative analysis, 31 (24.60%) presented significant differences between the two samples. Overall, findings suggest that SH cases between the two countries are more similar than they are different.